Hubungan Faktor End User Computing Satisfaction Terhadap Kepuasan Pengguna Sistem Informasi Di Rumah Sakit PKU Muhammadiyah Kota Yogyakarta: Analysis of the Relationship between End User Computing Satisfaction Factors and User Satisfaction of Information Systems at PKU Muhammadiyah Hospital, Yogyakarta City - Nur Sinta; Syam, Nur Syarianingsih (Universitas Ahmad Dahlan, 2022)
Background: According to the 2011 Minister of Health, everyhospitalisrequired to implement SIRS, so that a process of collecting, processing, and presenting hospital data can be integrated. In its implementation, SIMRS is required to improve the effectiveness and efficiency of a service system. One indicator of the success of the development of information systems is user satisfaction. A number of methods to measure user satisfaction, one of which is EUCS. The general purpose of the study is to analyze the EUCS factor on system user satisfaction, while the specific purpose of this study is to see if there is a relationship between the EUCS variable factors, namely content, format, accuracy, timeliness, and ease of use with satisfaction of hospital management system users at PKU Muhammadiyah Yogyakarta in 2021. Methods: The type of research used is quantitative research with a crosssectional design. Sampling using the lemeshow formula with the results of 245respondents. The selection of respondents used an accidental sampling technique with the research instrument using a questionnaire adopted from previous studies. Data analysis used univariate and bivariate analysis while the statistical test used was the chi square test with data categories normally distributed basedonthemedian value. Results: From the research conducted, it is found that there is a significant relationship between 5 EUCS variables, namely content, format, accuracy, timeliness and ease of use with SIMRS user satisfaction. The results of data processing usingthechisquaretestwereobtainedabout212(86.5%)respondents who stated they were satisfied and there were about 33 (13.5%) who said they were not satisfied with the SIMRS application. Conclusion: Overall, the five EUCS variables have a relationship and the use of the system states that they are satisfied with the My Hospital application.